Inverter-based resources dominated grid: Voltage and frequency stability in a weakly interconnected power system - Ndeye Khady Diop Dieng; Martin Wolter, Prof.Dr.-Ing.habil.; Lamine Thiaw, Professor; Adamou Ousmane Manga, Associate Professor (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
As power systems transition toward sustainable generation, the growing integration of inverter-based resources (IBR) poses challenges to secure power system operations, especially in grids with limited capacity. In this study, the large signal stability of the Senegalese transmission network in a condition of inverter-dominated grid is evaluated. Two IBR penetration rate scenarios were investigated: a base case with 57.7 % based on 2021 peak IBR and a second scenario with 66.8 % in DigSILENT PowerFactory. The voltage stability at critical buses and the frequency response of the system were analyzed against the grid code. The system response following a balanced triphase short circuit fault, where the impact of fault-clearing time and reactive power operation mode of PV plants was investigated. The frequency response is assessed following largest power infeed loss by plants technology (IBR or synchronous generator). The results demonstrate that inverter-dominated grid mainly impact frequency stability rather than voltage stability, with the disconnection of weaker PV plants during faults leading to underfrequency load shedding. High IBR penetration primarily resulted in weakening the connection point of the PV electrically distant from conventional power plants during faults. A fault clearing time exceeding the low voltage ride-through of PV plant and the cessation of reactive power injection by PV caused the trip of weaker PV plants. In summary a secure power system operation at 57.7 % and 66.8 % is achievable under the condition that the fault does not result in a generation loss that exceeds 5.2 % of the total dispatched power.